Kingdom. 7 - Hara, Yasuhisa, 1975- (VIZ Media, LLC, 2026)
"Xin is a war orphan in a poor village in the kingdom of Qin. He has big dreams of becoming the Greatest General Under the Heavens, and when his best friend's life is cut short by political machinations, Xin finds himself on a quest to do what no one has ever done before-unify China. With the Qin army severely outnumbered by the Wei army, their morale is starting to waver. But General Biao Gong isn't backing down, and he leads a final all-out, desperate attempt at victory. Xin and the other foot soldiers can only watch as the general and his cavalry descend upon the Wei army. That is, until a certain Qin general, who goes where he pleases, appears at Xin's side and eggs him on to join the fray..." -- Back cover.